Oxidative Stress as the Main Target in Diabetic Retinopathy Pathophysiology - Olvera-Montaño Cecilia; Castellanos-González José Alberto; Navarro-Partida José; Cardona-Muñoz Ernesto Germán; López-Contreras Ana Karen; Roman-Pintos Luis Miguel; Robles-Rivera Ricardo Raúl; Rodríguez-Carrizalez Adolfo Daniel (Journal of Diabetes Research)
Diabetic retinopathy (DR) is one of the most common complications of diabetes mellitus (DM) causing vision impairment even at young ages. There are numerous mechanisms involved in its development such as inflammation and cellular degeneration leading to endothelial and neural damage. These mechanisms are interlinked thus worsening the diabetic retinopathy outcome. In this review, we propose oxidative stress as the focus point of this complication onset.